Analisis Akurasi Website Pemerintah Provinsi Jawa Barat - Lila Latsmira; Yunita Prima Perwata (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Currently, the need for information is important in everyday life. The government plays a role in meeting the information needs of the community by providing access to information that is accurate, reliable and easily accessible. One effort to meet community needs is by providing communication channels such as official government websites, information centers, and others. The aim of this research is to assess whether a website meets standards as a source of accurate information. This research uses an exploratory study writing method. From the results of the analysis carried out by researchers on the West Java Government website (https://jabarprov.go.id/) using 20 indicators of information quality dimensions, it was found that overall the information quality of the website has been implemented well.